2020
DOI: 10.1111/exd.14148
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase inhibition rescues keratinocytes from elevated oxidative stress in a 2D atopic dermatitis and psoriasis model

Abstract: Emerging evidence suggests oxidative stress plays a role in the pathophysiology of both atopic dermatitis (AD) and psoriasis (PSO). We established in vitro models of AD and PSO skin, and characterized these models in regard to their oxidative stress state. Both AD and PSO model keratinocytes exhibited elevated reactive oxygen species (ROS) levels and accumulated more DNA damage than control cells after oxidative stress induced by 250 µmol/L H2O2. Elevated ROS levels and DNA damage accumulation could be inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Other NOX isoforms could also contribute to oxidative stress. In vitro studies have demonstrated that NOX4 is the main ROS source in human psoriatic fibroblasts and is essential for redox-mediated modulation of the metabolism in keratinocytes 90 , while inhibition of NOX1 in keratinocytes derived from the skin of atopic dermatitis patients significantly reduced ROS production 91 . Furthermore, NOX4 is highly expressed in endothelial cells and is involved in osteoarthritis, renal diseases and angiogenesis during ischemia, hypoxia and inflammation 92 - 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Other NOX isoforms could also contribute to oxidative stress. In vitro studies have demonstrated that NOX4 is the main ROS source in human psoriatic fibroblasts and is essential for redox-mediated modulation of the metabolism in keratinocytes 90 , while inhibition of NOX1 in keratinocytes derived from the skin of atopic dermatitis patients significantly reduced ROS production 91 . Furthermore, NOX4 is highly expressed in endothelial cells and is involved in osteoarthritis, renal diseases and angiogenesis during ischemia, hypoxia and inflammation 92 - 94 .…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is commonly treated by targeting TNFα signalling (Chima & Lebwohl, 2018), and Nox1 inhibition reduced inflammation and improved human keratinocyte survival in an experimental model of psoriasis (Emmert et al . 2020). The expression changes favouring 8D over 8C in psoriatic skin again suggest a compensatory response to downregulate pro‐inflammatory Nox‐dependent signalling.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a skin disease commonly treated by targeting TNFα signaling (Chima & Lebwohl, 2018). Inhibition of Nox1 reduced inflammation and improved human keratinocyte survival in an experimental model of psoriasis (Emmert et al ., 2020). Thus, the observed expression changes favoring LRRC8D over LRRC8C in psoriatic skin are again consistent with downregulation of Nox-dependent inflammation.…”
Section: Discussionmentioning
confidence: 99%